A method for a comprehensive lipidomic analysis of flaxseed (Linum usitatissimum) with the use of LC–Q-TOF-MS and dispersive micro-solid-phase (μDSPE) extraction. (1st July 2022) - Bakhytkyzy, Inal; Hewelt-Belka, Weronika; Kot-Wasik, Agata
Highlights: Flaxseed lipids (FL) were characterized using LC–MS-based lipidomic approach. New dispersive micro-solid-phase extraction method for FS lipidomics was developed. 148 lipids in 18 commercial flaxseed samples were identified and compared. PCA of 60 lipids confirmed by MS/MS discriminated brown and yellow flaxseeds. FL high in C18:2 and C18:3 fatty acids correlated with yellow and brown flax, respectively. Abstract: Flaxseed (FS) is one of the richest sources of α-linolenic acid oil and lignans, and it is suggested that the consumption of flaxseed may contribute to the prevention of certain chronic diseases such as many types of cancer, diabetes, cardiovascular diseases and cerebrovascular stroke. Here, we demonstrate a new method for comprehensive FS lipidome profiling with the use of LC–Q-TOF-MS and dispersive micro-solid-phase extraction. The effects of stationary phase amount, flaxseed amount and different organic solvents for non-polar lipid elution on the FS lipidome coverage were investigated. The developed and validated protocol allowed for improved monitoring of both polar and non-polar lipids simultaneously, overcoming the challenge of low- and high-abundance lipid species. Furthermore, the method was applied to characterize a set of brown flaxseed and yellow flaxseed samples, as well as flaxseed meal.